Application of probiotics in commercial layer diets: a review - Chowdhury, SD; Ray, BC; Khatun, A; Redoy, MRA; Afsana, AS (Bangladesh Journal of Animal Science, 2020)
Probiotics of various commercial preparations are being considered worldwide for poultry as performance enhancers and suitable alternatives to antibiotics. Much of the previous efforts to explore beneficial effects of probiotics were directed for commercial broilers and scientific information for commercial layer nutrition is limited in contrast to that of broilers. To our knowledge, whatever information is available, no attempt has been made as yet to make a comprehensive review of the effects of probiotics on layer chicken covering different aspects of production. This review is prepared by consolidating and updating information available in the literature covering laying performance, serum chemistry, egg quality and its safety aspects. Data generated from a number of studies clearly indicated that apart from a few exceptions, probiotics are found to be effective for the improvement of laying performance; serum biochemical parameters, egg shell and albumen quality and they are suitable for the production of safe eggs. Effect of probiotics on layers is mediated by boosting up gut health thereby creating an environment for better nutrient assimilation and thus an improvement of production and egg quality is achieved. Factors affecting such results need to be assessed more precisely since they contribute to some contradictions in the literatures. Nevertheless, the feed industry can rely on probiotics as quite safe for the production of quality feed to support commercial layer nutrition. Bang. J. Anim. Sci. 2020. 49 (1): 1-12